Reactions of 1-Arylbenziodoxolones with Azide Anion: Experimental and Computational Study of Substituent Effects; European Journal of Organic Chemistry; Vol. 2018, iss. 5 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Soldatova N. S. Nataliya Sergeevna; Postnikov P. S. Pavel Sergeevich; Valiev R. R. Rashid Rinatovich; Svitich D. Yu. Dmitry Yurjevich; Yusubova R. Ya. Roza Yavidovna; Yoshimura A. Akira; Wirth Th. Thomas; Zhdankin V. V. Viktor Vladimirovich (2018, 2018)
Title screen